Wagging through the snow - Berenson, Laurien (Berenson, Laurien. Melanie Travis mystery., 2017)
Melanie Travis needs a little peace from her busy life this Christmas. But the usual holiday hubbub is a joy compared to the killer surprise she finds tucked underneath the tree ... With a demanding teaching job at Connecticut's elite Howard Academy and five poodles scampering around the house, Melanie barely has energy for the upcoming Christmas rush. But she unwraps an unexpected challenge when her brother and ex-husband, elated by the recent success of their country cafe, make a spontaneous bid on a dilapidated pine tree farm. Although the ten-acre lot had been a popular seasonal destination while the original owner was still alive, it'll take some sprucing up-and a small miracle or two-before the neglected place is in shape for December. Unfortunately, the impromptu business venture goes cold when the group discovers a purebred Maltese whimpering in the snow-covered grove-right beside a dead body.